The Effect of Time Reading Activity (TRA) Strategy on Students' Reading Speed in Senior High School - Ayu Anastasya Aprilia; Tera Athena (Penerbit STKIP PGRI Bangkalan, 2024)
The strategy is very important in teaching so the teacher must be able to choose a strategy that suitable with students’ need. Time Reading Activity (TRA) which is design allow students to self-assess their reading, reading quickly under time pressure and answer several question. This strategy used to know the effect on students’ reading speed in SMA Darul Kholil. The method used in this study is pre-experimental design which is designed by using one group pre-test post-test. In this method the researcher only use one group in collecting data. The research conducted to all of students in X IPA with a total 24 students. The result of students pre- test and post-test show improvement. The score in minimum and maximum both of the test are increased. Not only that, the students reading times are faster with the mean of score pre-test 62.08 and the mean of post-test scores is 79.58. There is significant effect on students regarding Time Reading Activity strategy. This can be seen from the results of the paired sample t-test which show t-test value is greater than t-table. From has been counted through SPSS, the t-test value (8.668) t-table value (2.068) with significant value 0.000.